Automatic detection of vessel signatures in audio recordings with spectral amplitude variation signature. Issue 9 (26th July 2019) - Reis, Clausius D. G.; Padovese, Linilson Rodrigues; de Oliveira, Maria C. F.
Abstract: Sound emissions by ships and boats can strongly impact marine life, with potential to affect communications, breeding and prey and predator relationships. Automatic detection of boat signatures in underwater audio recordings is thus an important task. Automated solutions are particularly relevant for monitoring preservation areas where the presence of watercrafts is usually regulated. The task is particularly challenging because it requires distinguishing multiple overlapping acoustic events in typically noisy audio recordings. In this paper, we introduce an algorithm for boat and ship detection which computes an acoustic signature that captures the variance in the frequency amplitudes observed over the duration of the signal. We evaluated the algorithm on a database of underwater recordings collected at two conservation areas in the State of São Paulo, Brazil, with very good results, and also compared it with an existing solution. Besides being effective, the algorithm requires limited user input and no parameter fine tuning to handle diverse situations. It thus provides a solution to automate the detection of vessels, with potential applications for monitoring marine preservation areas.